Review of Brazilian species of Syneches Walker (Diptera, Hybotidae, Hybotinae), with description of ten new species - Soares, Matheus M. M.; Freitas-Silva, Rafael A. P.; Ale-Rocha, Rosaly (Zootaxa, 2021)
We increase the knowledge on the taxonomy of Brazilian Syneches describing 10 new species: S. amorimi sp. nov., S. barrettoi sp. nov., S. digitatus sp. nov., S. fasciatus sp. nov., S. flaviscutellatus sp. nov., S. fuscus sp. nov., S. nordestino sp. nov., S. plaumanni sp. nov., S. sinclairi sp. nov., and S. smithi sp. nov., and redescribing three species: S. catarinae Smith, 1962, S. luteus (Wiedemann, 1830) and S. tomentosus Smith, 1962. Syneches ruficollis (Walker, 1852) is proposed as a nomen dubium since the type is lost and the original description does not allow identification. An identification key, high-resolution images of relevant characters, short diagnoses and maps of geographic records for all 34 Brazilian species now included in the genus are provided, as well as a checklist for the South American species of Syneches.